Catalytic Autoxidation of Fatty Acid Methyl Esters from Jatropha Oil. (16th October 2014) - Endalew, Abebe K.; Kiros, Yohannes
Abstract : Metal catalysts for transesterification of vegetable oils can cause autoxidation side reactions which reduces the fuel quality of the biodiesel. On the other side, oxidation of highly unsaturated oils can open opportunities for the synthesis of other important renewable chemical products. This study reports catalytic oxidation of fatty acids of Jatropha curcas oil (JCO) by Li-CaO/Fe2 (SO4 )3 catalyst during transesterification at mild reaction conditions. The catalytic oxidation of the triglycerides was shown to be enhanced by the presence of lithium incorporated in the otherwise active catalyst combination of CaO/Fe2 (SO4 )3 used for high conversion into FAME. Matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF MS) was used to assess the reaction products.